Variables that influence teachers’ practice of differentiated instruction in Chinese classrooms: A study from teachers’ perspectives - Bi, Meijie; Struyven, Katrien; Zhu, Chang (Frontiers in Psychology, 2023)
As the diversity of students increases, differentiated instruction (DI) serves an increasingly significant function in meeting their individual learning needs. Emerging research has highlighted the value of inclusive teaching approaches to address students’ differences. The original Differentiated Instruction Questionnaire (DI-Quest; Coubergs et al., 2017) was designed to quantify teachers’ thoughts and behaviors through measurement of their DI philosophies and principles in classroom teaching. This study follows the DI-Quest model to investigate the factors that influence teachers’ practice of DI, taking into account their teaching experience, class sizes and school locations. The sample comprised 1,935 teachers from 150 national lower secondary schools in six provinces of central and western mainland China. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA), scale reliability, and invariance testing were conducted to explore and verify the factor structure of a Chinese mainland version of the DI-Quest (CN-DI-Quest). The empirical findings indicate that CN-DI-Quest is a valid and reliable instrument for future study of teachers’ DI philosophies, principles and practice. Moreover, the results of structural equation modeling revealed that teachers’ practice of DI (i.e., adaptive teaching) was explained largely by their ethical compass, flexible grouping, output=input, teaching experiences, and class size. Notably, teachers’ practice of DI (i.e., adaptive teaching) could not be predicted by growth mindset and school location. This study addresses gaps in the literature, since it provides empirical evidence regarding DI in Chinese mainland schools, offers material and suggestions for future research and provides recommendations useful to the professional advancement of Chinese teachers, including training programs and professional support.